Basic new born and antenatal screening for aspirational districts: unique methods of management and treatment of inherited disorders - Uppal, Komal; Joshi, Chandrika; Polipalli, Sunil Kumar; Kumar, Somesh; Jindal, Ankur; Gupta, Sangeeta; Verma, Amar; Kapoor, Seema (International Journal of Contemporary Pediatrics, 2024)
Background: Early screening, diagnosis and management program can contribute in reducing the burden of genetic disorders which can lead to early neonatal death or long-term disability in the vulnerable areas. UMMID (Unique Methods of Management and treatment of Inherited Disorders) and NIDAN (National Inherited Diseases Administration), aimed at developing a community level program for need assessment and to evaluate the feasibility of basic screening for some genetic/endocrine disorders in high-risk population. Methods: UMMID was carried out at the aspirational district Ranchi, Jharkhand for 3 years (2019-2022) to perform newborn screening (NBS) in <7 days old newborn babies for 5 metabolic disorders and to screen antenatal mothers for prevention of thalassemia and other hemoglobinopathies. Results: G6PD deficiency being more prevalent in Ranchi district out of five metabolic disorders screened. 13.6% of screen positive cases were confirmed positive for hemoglobinopathies. c.20 A>T is the most common mutation found among carriers. Conclusions: This initiative underscores the need of such screening programs in aspirational districts to manage and prevent these disorders effectively.